Interaction of Fusarium oxysporum f.sp. ciceri with Meloidogyne incognita on chickpea in two soil types - K. KRISHNAPPA, V. KRISHNA RAO1 and (Indian Phytopathology, 2002)
A pot experiment was conducted to investigate the interaction of F. o. f.sp. ciceri [F. o. f.sp. ciceris] with M. incognita on chickpea cv. Annegiri in 2 soil types (alfisol and vertisol). Inoculation of chickpeas with fungus, either with nematodesor 7 d before or after nematode inoculation, resulted in significant reduction in FW and DW of shoot and FW of root as well as an increase in wilt incidence compared with plants inoculated with the fungus alone. Nematode multiplication and root-knot incidence were higher in the alfisol and fungal growth and wilt incidence were higher in the vertisol.